O turismo de sol e praia no litoral sul de Sergipe : uma análise sob a perspectiva dos modelos Sistur e Talc - Lima, Letícia Bianca Barros de Moraes (2011)
This theory has as central objective to analyze the relationship of the phenomenon of the sun and beach tourism in the South Coast of Sergipe and the subject of research (usual tourist, second residence s tourism and local population), it constitutes an analysis of the spacetemporary diffusion of the sun and beach tourism and the manifestation of the second residence in the South Coast of Sergipe under the perspective of the models SISTUR of Beni (1988) and TALC of Butler (1980). The study had as conductive thread the relationship geography and tourism with emphasis in the debate of the categories of the science geographical territory, landscape and place. The research had as base the deductive method orientated by a systemic vision and the investigation process adopted the methodological procedures of rising bibliographical, documental, cartographic and statistical; elaboration of the study itinerary; field research; analysis and interpretation of the results. The research instruments used in field were questionnaires with open and closed subjects quantified by the scale of Likert in order to measure the degree of agreement/disagreement of the subject of research. The research elucidates the appearance of the sun and beach tourism in the occident from his invention to his structuring in Brazil and in the Northeast emphasizing scientific studies about the environment and the tourism, besides presenting the territorial and tourist scenery of the South Coast of Sergipe, approaching the historical process of occupation, the territorial system and the dynamics demographic, environmental and socioeconomic. The analysis of the instruments of territorial planning i) Coastal Management Program (GERCO); ii) Program of Development of the Tourism in the Northeast (PRODETUR); iii) Project ORLA and their Plans of Municipal Intervention; iv) Area of Environmental Protection (APA) South Coast; v) Economical-Ecological Zoning (ZEE); and vi) Master plans identified the main impacts of these in the tourist activity of the destiny. The results of SISTUR demonstrated that the basic and tourist infrastructures of the South Coast of Sergipe are not still enough to attract a maintainable flow of sun and beach tourist, and the application of TALC verified that the current apprenticeship of the sun tourism and beach is in the beginning of the apprenticeship of the development in the South Coast of Sergipe, characterized by the prevalence of the tourism of second residence. The territorial and tourist model of the South Coast of Sergipe is marked by the territorialized dynamics of the second residence s tourism that added to the investments avidness mainly of PRODETUR I and II they stimulated the growth and the consolidation of the production of this modality of tourism in the area. This way, it is ended that the partner-space practices of the leisure and second residence s tourism they accelerated the process of transformation of the landscape and they will establish the production of new tourist territories in the South Coast of Sergipe. Consequently, this study moves forward in the understanding of the models space - storms and of the politics returned to the valorization of the areas of beaches.